2022
DOI: 10.1002/chem.202202081
|View full text |Cite
|
Sign up to set email alerts
|

Branched Tertiary Amines from Aldehydes and α‐Olefins by Combined Multiphase Tandem Reactions

Abstract: This study presents the transformation of olefins to branched amines by combining a hydroformylation/aldol condensation tandem reaction with the reductive amination in a combined multiphase system that can be recycled 9 times. The products are branched amines that are precursors for surfactants. Since the multiphase hydrofomylation/aldol condensation system has already been studied, the first step was to develop the partial hydrogenation of unsaturated aldehydes together with a subsequent reductive amination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Besides the hydroformylation, the hydrogenation of C 14 aldol products was tested, to investigate the reaction scope of this recycling method. 2-Pentylnon-2-enal (C 14 aldol product) was synthesized from heptanal according to a literature procedure reported by Vorholt et al 33 During the hydrogenation, a saturated aldol product in which only the double bond is hydrogenated (2-pentylnonanal) and the saturated alcohol after a subsequent hydrogenation of the aldehyde (2-pentylnonanol) are formed (reaction scheme, Table 3). This group of hydrogenated aldol products can be used in the production of surfactants, as plasticizer alcohols or in further chemical processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the hydroformylation, the hydrogenation of C 14 aldol products was tested, to investigate the reaction scope of this recycling method. 2-Pentylnon-2-enal (C 14 aldol product) was synthesized from heptanal according to a literature procedure reported by Vorholt et al 33 During the hydrogenation, a saturated aldol product in which only the double bond is hydrogenated (2-pentylnonanal) and the saturated alcohol after a subsequent hydrogenation of the aldehyde (2-pentylnonanol) are formed (reaction scheme, Table 3). This group of hydrogenated aldol products can be used in the production of surfactants, as plasticizer alcohols or in further chemical processes.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was observed by Vorholt et al previously. 33 By applying vacuum to the catalyst phase at 60 °C after the third and fifth run, the CO was (partially) removed and the hydrogenation showed significantly better conversions increasing from 10% in run 1 to 63% in run 6. Additionally, the remaining nonanal from the previous run was also partly hydrogenated to nonanol during the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect of carbon monoxide on the suppression of alcohol formation has already been observed in the literature. 2,6 Given that the CO addition had a much more significant influence than a reduction of catalyst concentration, it can be concluded that the CO does not act by partially deactivating the catalyst but rather by changing the catalyst species, which can also be observed by the color change of the catalyst solution from red (without CO) to yellow (with CO); see SI for photos.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Aliphatic amines are valuable products in the chemical industry, finding various applications such as in pharmaceuticals, surfactants, and agrochemicals. , One efficient way of producing amines is catalytic reductive amination (RA), in which amines are alkylated using aldehydes or ketones, yielding the desired amine. RA proceeds via an initial condensation and final catalytic reduction of the intermediate enamine or imine.…”
Section: Introductionmentioning
confidence: 99%